PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PEMBELAJARAN IPS DI MADRASAH IBTIDAIYAH - Susilawati, Samsul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
IPS Integrated Learning is essentially a human activity of daily life, shaped by the social environment and the growing of a civilization. Truth IPS Integrated formed explicitly by the "social agreement", the new rules formed from the old rules that have been agreed upon and accepted by the people truth. IPS Learning Integrated into the joints of the life and activities of the Integrated IPS The range of material can only be understood if the students have the opportunity to build (construct) and develop keselurahan aspects of the integrated IPS material that can be achieved through appropriate learning patterns one of them is a type of cooperative learning jigsaw.Keywords: Constructivism, Cooperative learning jigsaw type